Draft Plan for Darjeeling Hill Areas 1985-90 Volume II Schematic Details Government of West Bengal - Planning Commission (Planning Commission, 1977)
Agriculture Development West Bengal Forest Development Corporation District Industries Centers Road and Communication Social and Community Service Municipal Service Environment survey and Research Development and Planning Department Hill Affairs Branch Secretariat Darjeeling Darjeeling Hill Areas 1985-90 Volume II Schematic Details Government of West Bengal.
Government of West Bengal
Development and Planning Department Hill Affairs Branch Secretariat Darjeeling
Keywords: Agriculture Development; West Bengal Forest Development Corporation; District Industries Centers; Road and Communication; Social and Community Service; Municipal Service; Environment survey and Research; Principal Agricultural Officer Darjeeling; Plant Protection Scheme; Development of Pisciculture; Watershed Management